Facial Prominence of Political Candidates: Gender Differences in Private and Public Pages on Facebook Profile - Valmori, Alessia; Garau, Tania; Carraro, Luciana; Castelli, Luigi (Frontiers in Psychology, 2021)
The face of a person is an important source of communication and information especially for politicians who are continuously portrayed through media. Voters may use this information to form an impression about the candidates and several inferences may be drawn. Within this frame, research has largely investigated gender differences. One line of research has focused on the facial prominence of people portrayed in pictures, describing a tendency to portray men with a higher face prominence as compared to women. This bias has been defined as the face-ism effect and it has a key influence on the perception of dominance, competence, intelligence, and ambition of the portrayed individuals. Several studies in recent years analyzed the differences between the self-representation of men and women in social media, but no study specifically focused on politicians directly comparing two different types of profiles: private vs. public. In two studies, we analyzed differences in face-ism index comparing male and female politicians both for pictures posted in private and public Facebook accounts. In Study 1 results showed that no difference emerged between men and women engaged in politics when considering public pages; however, when private profiles are analyzed, women displayed a higher face-ism index than their male counterparts. Study 2 partially confirmed results from Study 1 considering Italian politicians. Overall, current results showed a different pattern as compared to previous studies suggesting an increase in perceived agency and dominance for female candidates, particularly emphasized in their private profiles.